Efektivitas Transcutaneous Electrical Nerve Stimulation dan Manual Terapi terhadap Penurunan Nyeri pada Pelari Marathon dengan Patellofemoral Pain Syndrome: A Systematic Review - Adelia Gita Pratiwi; Suci Nurmarisa; Jacinda Nasya Nathania Zahra (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract Patellofemoral Pain Syndrome (PFPS) is a musculoskeletal disorder characterized by anterior knee pain and commonly experienced by long-distance runners, including marathon runners. This condition may cause decreased knee function, physical activity limitations, and reduced athletic performance. This study aimed to analyze the effectiveness of Transcutaneous Electrical Nerve Stimulation (TENS) and manual therapy in reducing pain and improving knee function in marathon runners with PFPS using a Systematic Literature Review (SLR) approach. Articles were obtained from Google Scholar, PubMed, and ScienceDirect databases published between 2020 and 2025 using predetermined inclusion and exclusion criteria. A total of 10 relevant journals were analyzed focusing on TENS intervention, manual therapy, and therapeutic exercises related to pain reduction and improvement of knee function. The findings showed that TENS was effective in reducing pain intensity through pain modulation mechanisms in the nervous system, while manual therapy and therapeutic exercises improved knee function, proprioception, and functional activity in patients with PFPS. The combination of TENS with exercise therapy and manual therapy provided more optimal rehabilitation outcomes compared to single interventions. Based on the review results, it can be concluded that TENS and manual therapy are effective physiotherapy interventions for reducing pain and improving knee function in marathon runners with PFPS. Keywords: Patellofemoral Pain Syndrome, TENS, Manual Therapy, Marathon Runners, Physiotherapy, Rehabilitation